Role of Structures Inspired by Nature to achieve Sustainable Architectural Buildings Case Studies: National Museum of Qatar, El-Bahr Towers, Eden Project (Texas Journal of Engineering and Technology, 2024)
The built environment is considered to be one of the major causes of the negative environmental impacts, consuming materials, using energy resources, and emitting green house gases. Therefore, architects and engineers are always seeking more sustainable design solutions. This is where biomimicry has a powerful role. Biomimicry is a science that studies nature to solve human problems as it has abundant structural solutions that can help in evolving a complex form which was the focus of this paper. This paper is seeking sustainable structural solutions by studying and analyzing sustainable architectural cases in which their structural systems were inspired by nature with less negative impacts on the environment. As a result of the study, some guidelines were concluded which can be employed into the design of the structural system to obtain sustainable architecture showing how nature can be a guide for a more sustainable environment in the future.